Handbook of international relations - Carlsnaes, Walter; Risse-Kappen, Thomas; Simmons, Beth A. 1958- (Thousand Oaks, California SAGE Publications, 2013)
Drawing together a team of the world's leading scholars, this major new handbook provides a state-of-the-art review and guide to the study of international relations
Previous edition in print: 2002
Includes bibliographical references and index
Keywords: International relations